Left and right otolith morphometry variation of bigeye scad, Selar crumenophthalmus (BLOCH. 1793) from the Sibuyan sea, Philippines. - Nono, Hazel Joy
Otoliths are known as calcareous concretions that, along with the semicircular canals, comprise the inner ear of teleost fishes. Their morphometry generally differs across species and there have been several researches that have examined this particular aspects in detail. Neverheless, there is a lack of studies that examine the morphometric variation of the left and right otoliths in certain fish group. In this study, the left and the right otoliths in certain fish groups. in this study, the left and the right otoliths of bigeye scad (Selar crumenophthalmus) from the Sibuyan Sea were analyzed for differences in morphometry. A total of ten direct otolith descriptors (otolith length, OL; otolith height, OH; otolith area, OA; otoloth perimeter, OP; otolith weight, OW; rostrum length, RL; rostrum height, RH; caudal length, CL; ostium length, OSL; sulcus length, SL) and eight derived otolith descriptors (rectangularity, RE; squareness,SQ; ellipticity, EL; roundness, RO; aspect ratio, AR; form factor, FF; compactness, CO; circularity, CI) were used to collect the data for this study. The obtained values were subsequently subjected to Pearson correlation, alletry correction, Shapiro-Wilk test, paired samples t-test, Wilcoxon signed rank test, and principla compnent analysis (PCA) to achieve a valid comparative analysis of the two otolith sides. Raw data reveals that left otoliths were heavier and had longer as well as wider rostrums. They similarly exceedright otoloiths in terms of area, squareness, ellipticity, roundness, aspect ratio, and form factor. Right otolith, however, were determined to be generally longer, wider, and superior than their left counterpartsin terms of parameters, caudal length, ostium length, sulcus length, compactness, and circularity. Further statistical anaysis reveal that at 52.53% of otolith parametervariation, the left and right otoliths are different with the descriptors. CO, OSL, OP, OL, SL, OH, CL and OA being the best indicators of their distinction. Moreover, SQ and CL were revealed to be unusable descriptors i separating the left and the right otoliths. These results contradict the findings of Taliawo et al. (2018) and Bahri et al. (2018) who also examined the left and the right morphometry of S. crumenophthalmus but found no variation between them. Differences in variables condidered, dissimilarity in sampling sites, and variation in descriptors utilized are determined to be possible reasons behind this deviation of results. Further investigationof this aspect integrated with the examinations of modified variables are recommended to fully establish morphometry of S. crumenophthalmus in the Philippines waters.